Implementasi Pola Asuh Demokratis dalam Keberhasilan Sikap Prososial Anak Usia 5-6 Tahun di Kelompok B TK Miftahul Ulum XXVII Ambender, Pegantenan - Mukarromah, Ulfatul; Farida, Siti (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Instilling a prosocial attitude in children is not easy, it must be done painstakingly and understandingly. Parenting is the most important factor in the formation of children's prosocial attitudes. This study aims to determine the application of parents' democratic parenting style to the success of prosocial attitudes of group B children in Miftahul Ulum XXVII Kindergarten. This research uses qualitative descriptive methods by describing data in accordance with facts in the field so that the data becomes clear and accurate. The data collection technique uses 3 ways, namely observation, interviews, and documentation. The primary data sources in this study were parents and teachers. While secondary data sources researchers use theses, articles and journals. Parents of prosocial children in Miftahul Ulum XXVII Kindergarten on average use democratic parenting patterns in their children's care, there is indeed a close relationship between democratic parenting and children's prosocial attitudes.